Exploring the property development risks in modern South Africa and their impact on property development projects. - Nomlomo, Chulumanca (Department of Construction Economics and Management, 2026)
Property development in South Africa is inherently capital intensive and risky but has the potential to reward brave developers through high returns. The risks that property developers face is multi-layered and unique to each project, requiring discernment on the part of the developer. However, projects likely to yield high returns are fairly easy to identify, and mitigation strategies can be implemented to ensure that property development projects are completed within cost and time limitations, and to a high standard. The intention of this study was to identify the property development risks in modern South Africa and the impact of these risks on property development viability, and to make recommendations on how identifiable risks may be mitigated in the property development sector. Property professionals were selected as participants in this study. These included senior executives in some of South Africa's largest development companies, people in the property finance industry, and those who deal daily with property development projects. All participants were interviewed one-on-one. This strategy yielded insight into the research questions, since participants were able to draw directly from their personal experiences. Responses in the interviews answered all the research questions and thus informed the recommendations made in this study. The study revealed that the main risks to property development projects in South Africa are political and socio-economic factors, municipal inefficiencies, social unrest, increases in municipal costs and materials, and lack of consistent power supply from Eskom. Increased capital costs in property development projects have reduced returns for property developers, forcing many to consider investing outside of South Africa. This was identified as the main impact of the risks on property development projects. The recommendations made in this study to mitigate property development risks are government subsidies for bulk infrastructure, fixing of material prices, greater engagement of all stakeholders in the property development process, ensuring that construction contractors have the required capacity and skills, greater use of technology in property development projects, and municipal rebates for property developers, in order to incentivise development. It is also recommended that in all property development projects, developers factor in potential cost increases.